Reducing current distortion in indirect matrix converters operating in boost mode under unbalanced input conditions - Choi, Dongho; Bak, Yeongsu; Lee, Kyo Beum (Journal of Power Electronics, 2019)
This paper presents a control method for reducing the current distortion in an indirect matrix converter (IMC) operating in boost mode under unbalanced input conditions. IMCs operating in boost mode are useful in distributed generation (DG) systems. They are connected with renewable energy systems (RESs) and the grid to transmit the power generated by the RES. However, under unbalanced voltage conditions of the RES, which is connected with the input stage of the IMC operating in boost mode, the input-output currents are distorted. In particular, the output current distortions cause a ripple of the power, which is transferred to the grid. This aggravates the reliability and stability of the DG system. Therefore, in this paper, a control method using positive/negative sequence voltages and currents is proposed for reducing the current distortion of both side in IMCs operating in boost mode. Simulation and experimental results have been presented to validate effectiveness of the proposed control method.
Keywords: Boost mode; Current distortion; Indirect matrix converter; Sequence voltages and currents; Unbalanced input conditions; Boost mode; Current distortion; Indirect matrix converter; Positive/negative sequence voltages and currents; Unbalanced input conditions